1901 Utah Laws 97-98, ch. 96, §§ 1-3 - (:unkn) unknown (My University, 1901)
Prohibited the construction and possession of any "infernal machine," defined as a device with a loaded firearm that is capable of igniting when moved, handled, or opened.
Keywords: TRAP GUNS